The Influence of Microalgae Fertilizer on Soil Water Conservation and Soil Improvement: Yield and Quality of Potted Tomatoes - Chao Li; Yaqi Liang; Qingfeng Miao; Xiang Ji; Pengcheng Duan; Dong Quan (Agronomy)
We aim to study the impact of microalgae fertilizer on soil nutrients, water conservation and crop yield and quality while also determining the optimal ratio of microalgae fertilizer to chemical fertilizer. Using “Xinoufen No.9” tomatoes as the test subject, we conducted pot experiments with four different treatments: control with 100% chemical fertilizer (CK), T1 (25% microalgae fertilizer + 75% regular chemical fertilizer), T2 (75% microalgae fertilizer + 25% regular chemical fertilizer) and T3 (100% microalgae fertilizer). The results show that an increased application of microalgae fertilizer enhanced the soil organic matter, ammonium nitrogen, available phosphorus and potassium content. T3 showed the most improvement followed by T2. The co-application of microalgae fertilizer with chemical fertilizer can significantly increase the stem girth, plant height and yield of tomatoes. At the same time, microalgae fertilizer effectively regulates leaf stomatal conductance, promoting tomato leaf respiration. As the stomatal conductance increases, the transpiration rate and net photosynthesis rate of all treatments improve, followed by a decline in intercellular CO2 concentration, with T2 exhibiting the best performance. Among all treatments, T2 treatment yielded the highest per-plant production (0.630 kg), followed by T3 (0.521 kg). This is because the microalgae fertilizer promotes the distribution of photosynthetic products to the fruit, enhancing the yield and quality of tomatoes. Additionally, the microalgae fertilizer also increases the content of soluble sugars, soluble protein, vitamin C and lycopene in the fruit while reducing the nitrate content. Compared to the control group CK, T2 increases the content of soluble sugars, vitamins and lycopene by 26.74%, 39.29% and 158.31%, respectively. Microalgae fertilizer also helps to improve soil water and thermal conditions, enhancing the water-use efficiency of tomatoes. Compared to CK, the water-use efficiency of T2 treatment increased by 54.05%. Correlation analysis indicates that water and fertilizer factors significantly affect tomato yield, with a correlation exceeding 70%. The net photosynthesis and transpiration rates significantly influence fruit quality, with correlations above 80%. By applying microalgae fertilizer, the efficiency of water and fertilizer use can be effectively improved, thus achieving the goal of water conservation and quality enhancement. Therefore, through comprehensive analysis, using the membership function method of indicators such as soil environment, crop yield, fruit quality and water-use efficiency, it is concluded that T2 is the optimal fertilization treatment. This study provides theoretical support for the application of microalgae biofertilizer technology in the cultivation of tomatoes and other vegetables in the northern, cold and arid regions.